Rice Farming Process and Peasant's Da'wah Strategy in Bulukumba - Mahmuddin, Mahmuddin; Nasriah, St. Nasriah (Jurnal Adabiyah, 2020)
This study analyzes the procession of rice planting in Bulukumba and discovers the propaganda strategy in it. This research is qualitative research with a da'wah strategy approach. Data sources are farmers in Bulukumba and data collection is observation, interviews, questionnaires, and documentation. Data processing and analysis techniques consist of three steps: data reduction, data presentation, and research conclusions. The results showed that the rice planting procession in Bulukumba determined a good day to start planting rice, preparing seeds, soaking, storing and sowing seeds, working in the fields, planting, harvesting, and thanksgiving parties. Da'wah strategies are shown in six points: 1) determination of good days, 2) nursery systems in the form of a selection of the best seeds, 3) storage and the procession of sowing, 4) start working in the fields, 5) planting and harvesting, and 6) thanksgiving parties.تهدف هذه الدراسة إلى تحليل مسار زراعة الأرز في بولوكومبا واكتشاف استراتيجية الدعوة. هذا البحث نوعي بمقاربة استراتيجية الدعوة. كان مصدر البيانات الفلاحين في بولوكومبا وكان جمع البيانات الملاحظة والمقابلة والاستبيان والتوثيق. كانت تقنيات معالجة البيانات وتحليلها من ثلاث خطوات: تقليب البيانات، وعرض البيانات.   ونتانج  البحث. أظهرت النتائج أن مواكب زراعة الأرز في بولوكومبا كانت تحدد يومًا جيدًا لبدء فتح زراعة الأرز، وتحضير البذور، ونقع البذور، وتخزينها وزرعها، والعمل في الحقول، والزراعة، والحصاد، وحفلات الشكر. ظهرت استراتيجيات الدعوة في ست نقاط: 1) في تحديد يوم جيد، 2) في نظام الشتلات يمكن أن يكون على شكل اختيار أفضل البذور ، 3) في نقع موازين التخزين والبذر ، 4) في بدء العمل على حقل الأرز ، 5) في الزراعة والحصاد ، و 6) في حفلات الشكر.Penelitian ini menganalisis prosesi penanaman padi di Bulukumba dan menemukan strategi dakwah di dalamnya. Penelitian ini adalah penelitian kualitatif dengan pendekatan strategi dakwah. Sumber data adalah petani di Bulukumba dan pengumpulan data adalah observasi, wawancara, kuesioner dan dokumentasi. Teknik pengolahan dan analisis data terdiri dari tiga langkah: reduksi data, penyajian data, dan kesimpulan penelitian. Hasil penelitian menunjukkan bahwa prosesi penanaman padi di Bulukumba menentukan hari yang baik untuk memulai penanaman padi, menyiapkan benih, merendam, menyimpan dan menabur benih, bekerja di ladang, menanam, memanen, dan pesta ucapan syukur. Strategi dakwah ditunjukkan dalam enam poin: 1) penentuan hari yang baik, 2) sistem pembibitan dalam bentuk pemilihan benih terbaik, 3) penyimpanan dan prosesi menabur, 4) mulai bekerja di sawah, 5) menanam dan memanen, dan 6) pesta ucapan syukur.